Progressive systemic sclerosis with unilateral osteolysis of the mandible: a unique case report and review - Lusi Epsilawati; Chrisna Ardhya Medika; Eddy Hermanto (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This case report is aimed to discuss case findings of Progressive Systemic Sclerosis (PSS), an overview of the characteristics in the form of osteolysis on one side of the mandible, and a theoretical review. Case Report: A 30-year old male patient came to an oral surgeon after tooth extraction. Clinical extraoral examination revealed hyperpigmentation on the right side of the face. A radiological study showed widening periodontal space on posterior teeth, and the angles of the mandibular arch, the jaw branch and the mandibular condyle neck were dissolved in the form of bone resorption. Conclusion: Characteristics of Progressive Systemic Sclerosis (PSS) in radiographs appear in the form of expansion of the periodontal space and osteolysis of the mandibular angle, branch, and even condyle. This disease is caused by an autoimmune disease that affects the entire body, but it can manifest on one side of the body.